Edukasi Penanaman Cabai Untuk Mahasiswa Baru Biologi Dengan Media Polybag Untuk Pemberdayaan Pertanian Di Universitas Islam Negeri Mataram - Baiq Melinda Utari; Rudi Ariatma; Edi Muhamad Jayadi; Ulfa Nurwiana; Mai Rizali; Muhamad Yul Fikrian; Muamar Kadafin (Aksi: Jurnal Pengabdian Masyarakat, 2024)
This article contains education about planting chilies for New Biology Students using polybag media. The aim is to provide insight and practical skills regarding chili cultivation to new students of the Biology Study Program at UIN Mataram, so that they have basic abilities in growing horticultural plants. The method used is by reviewing relevant literature regarding chili cultivation techniques using polybags and husks as media. The tools and materials prepared include chili seeds, polybags, a mixture of husks and soil, and embrat as a watering tool. The results of this activity include various achievements in terms of education, practical skills, and empowerment of the campus community. This program can increase new students' understanding of polybag media-based agriculture and provide direct experience in the practice of chili cultivation. Through this training, students not only gain theoretical knowledge, but also practical agricultural management skills, which are relevant to the needs of the world of work and everyday life. From an economic perspective, planting chilies in polybags also opens up opportunities for students to learn about the commercial potential of horticultural crops. From the results of this activity, it can be concluded that the practice of community service using polybags and husks was successful in providing new students with a good understanding of chili planting techniques in the campus environment.